2012
DOI: 10.1039/c2sm25473e
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation and sorting of membrane proteins using patterned diffusion-aided ratchets with AC fields in supported lipid bilayers

Abstract: We present ratchets capable of directing the movement of charged components within supported bilayer lipid membranes. These ratchets make use of asymmetrically patterned features and AC electric fields, and have been demonstrated to transport charged species such as lipids and transmembrane proteins between two reservoirs. Proteins were present in both orientations in the membrane, with only those with their extra-membranous domain orientated away from the glass substrate being mobile. Proteins in the mobile o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Recently, we have demonstrated that charged lipids and a “simple” transmembrane protein can be concentrated in SLBs by using a “fish-trap” structure in conjunction with an ac electric field . We have also shown the directed transport and orientational sorting of transmembrane proteins by using double-sawtooth ratchet patterns . However, our previous work has two major shortcomings.…”
mentioning
confidence: 96%
“…Recently, we have demonstrated that charged lipids and a “simple” transmembrane protein can be concentrated in SLBs by using a “fish-trap” structure in conjunction with an ac electric field . We have also shown the directed transport and orientational sorting of transmembrane proteins by using double-sawtooth ratchet patterns . However, our previous work has two major shortcomings.…”
mentioning
confidence: 96%
“…The polymeric bilayer scaffolds that confine the hybrid thylakoid membrane can potentially enhance the membrane stability by supporting the fluid membrane from the side. Furthermore, the framework would be utilized to transport and concentrate the membrane-bound components by applying electric fields. , In the present study, we incorporated the whole thylakoid membrane, but it would be interesting to incorporate appressed (grana) and nonappressed (stroma lamellae) thylakoid membranes separately for concentrating some of the membrane components. At the same time, there are some technical limitations present in the patterned thylakoid membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Yoshina-Ishii and Boxer continued this work by showing that it was possible to manipulate lipids within membrane arrays . More recently, Cheetham and Roth and co-workers published a series of papers in which ratchet structures were fabricated by photolithography and microcontact printing for the movement and concentration of both lipids and membrane proteins within SLBs. …”
Section: Introductionmentioning
confidence: 99%